A Critical Review on the Book Islam in Russia: The Politics of Identity and Security - Bahram Navazeni (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
This is a review of the book "Islam in Russia: the politics of identity and security” by Shirin T. Hunter, the Iranian-American Professor of Georgetown University, in collaboration with two of the researchers at the Center for strategic and international studies, Jeffrey Thomas and Alexander Melikishvili, published in New York in 2004. A translation of this work is done by Elahe Koulaei, Professor at Tehran University, and two of his colleagues, Seyedeh Motahare Hussein and Asma Moini by Nei press in Tehran. Although the book may not be considered as the main textbook for political science course subjects, but may certainly be acknowledged as holding valuable information about the Soviet Government and politics, the big power's foreign policy, in all branches of BA, MA and PhD fields of political science, international relations, and regional studies. This article is also trying to introduce this work and its authors and translators, as well as critically analyze the structural and contextual weakness and suggest some corrective tips for the next edition of it.